Phenotypic Characterization and Whole-Genome Analysis of a Novel Bacteriophage HCF1 Infecting Citrobacter amalonaticus and C. freundii - Kumar, Prince; Meghvansi, Mukesh K.; Kamboj, Dev V. (Frontiers in Microbiology, 2021)
Citrobacter species often occur in sewage, food, soil, wastewater, and in the intestinal tract of animals and humans. Citrobacter spp. cause urinary tract infections and infantile meningitis in humans. Due to the presence of plasmid-encoded resistance genes, Citrobacter spp. are often resistant to many antibiotics. In this study, Citrobacter virus HCF1, a novel virulent bacteriophage capable of killing C. amalonaticus and C. freundii, was isolated from the sewage water. The isolated bacteriophage was characterized with respect to transmission electron microscopy, one-step growth curve, host range, in-vitro efficacy, storage stability, and environmental stress tolerance. The one-step growth curve analysis revealed that the latent period of HCF1 was 30 min and the estimated burst size was 121 PFU per bacterial cell. Host range testing indicated that the HCF1 was specific to the Citrobacter genus. In-vitro efficacy assay in the effluent of an anaerobic biodigester showed that the HCF1 completely eliminated the host within 4and5 h at MOI:100 and MOI:10, respectively thereby indicating its potential for combating C. amalonaticus infections. The isolated bacteriophage is considerably stable and tolerant to environmental stress. Furthermore, the complete genome of HCF1 was sequenced using Oxford Nanopore sequencing and the data were subjected to detailed bioinformatic analyses. NCBI-BLASTn analysis revealed that the HCF1 genome had a query coverage of 15 % – 21% and a maximum similarity of 77.27% – 78.49% with 11 bacteriophages of the Drexlerviridae family. Detailed bioinformatic analysis of the genome profile suggests that HCF1 is a novel T1svirus belonging to the Tempevirinae subfamily of the Drexlerviridae family.